Rural Families and Households in Post-Socialist Transition: Serbian Experience - Čikić, Jovana; Petrović, Marica (Eastern European Countryside, 2024)
Rural families and households make a basic framework for understanding the rural way of life. This relation is especially interesting under the recent and difficult post-socialist transition in places such as Serbia. Previous research has shown that the transition and its benefits are not distributed equally. This has induced social and economic disparities, at the expense of the social attractiveness of rural areas. These disparities have influenced characteristics of Serbian rural families and households, their survival strategies and their roles in the reproduction of the rural way of life. We started research with three assumptions: a) depopulation of Serbian rural areas continues under the post-socialist transition, b) transitional risks produce partial retraditionalization of Serbian rural family relationships, and c) characteristics of Serbian regions affect characteristics of rural families and households. The analysis confirmed rural depopulation. In the decade 2002–2011, there was the most significant decline ever in the number of Serbian rural families. This signified the negative impact of transition on rural areas. Besides this, the research confirmed that contemporary Serbian rural families and households still have some traditional features (multiple generations, relics of the role of head of the traditional rural family) which enable them to cope with transitional risks. A third finding proved that characteristics of Serbian rural families and households depend on regional characteristics.